Observation Patterns: Data and Charts from Eye-Tracking Study - Hamid Reza Akaf (20695655) (2025)
his data set explores the visual attention patterns of participants when observing heritage and modern facades, focusing on the influence of educational background. The study includes eye movement data collected from participants and presents it in a comprehensive manner through 18 tables and 16 charts.